tph Resto Balita Sebagai Lokasi Literasi Gizi Bagi Ibu Balita Dalam Mendukung Desa Sehat Di Kelurahan Karanganyar Kecamatan Neglasari Kota Tangerang - Titus Priyo Harjatmo; Pritasari; Nuraini Susilo Rochani; Tugiman A; Rina Efiyanna; Alfiantani Nugroho (CV. Multi Kreasi Media, 2022)
Stunting is the result of malnutrition in the long term that causes intellectual impairment and linear growth (Waterlow, 1972). In Indonesia, around 37% or nearly 9 million children under five are stunted (Riskesdas 2013) and this is the 5th largest prevalence of stunting in the world. The Nutrition Status Monitoring (PSG) conducted by the Ministry of Health in 2016 found that 27.5% of children under five years (toddlers) and 21.7% of children under two years were stunted. This causes them to get sick easily, have a shorter body posture than toddlers their age, do not have adequate cognitive abilities, so that it is not only detrimental to individuals but also detrimental to long-term socio-economic conditions for Indonesia. Cadres have a fairly important task in the implementation of Posyandu activities. The duties of cadres carried out before Posyandu Opening Day include: 1) Preparing for the implementation of Posyandu activities, 2) Disseminating information about Posyandu opening days through local community meetings or circulars, 3) Dividing tasks between cadres, including registration, weighing, recording, counseling , providing additional food, as well as services that can be carried out by cadres. Given the importance of cadre duties, skilled cadres are needed in carrying out cadre duties, especially in carrying out early detection of stunting children. Therefore, community service activities were carried out with the topic